2014
DOI: 10.1007/s00894-014-2417-z
|View full text |Cite
|
Sign up to set email alerts
|

Core-dependent and ligand-dependent relativistic corrections to the nuclear magnetic shieldings in MH4−n Y n (n = 0–4; M = Si, Ge, Sn, and Y = H, F, Cl, Br, I) model compounds

Abstract: The nuclear magnetic shieldings of Si, Ge, and Sn in MH(4-n) Y(n) (M = Si, Ge, Sn; Y = F, Cl, Br, I and n = 1-4) molecular systems are highly influenced by the substitution of one or more hydrogens by heavy-halogen atoms. We applied the linear response elimination of small components (LRESC) formalism to calculate those shieldings and learn whether including only a few of the leading relativistic correction terms is sufficient to be able to quantitatively reproduce the full relativistic value. It was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(133 citation statements)
references
References 31 publications
(51 reference statements)
8
125
0
Order By: Relevance
“…The electronic mechanisms involved in the HAVHA effect are treated in more detail in a submitted manuscript. 66 In this article we show the importance of such effect on magnetic shieldings in tin and lead tetrahalides family of compounds.…”
Section: 62mentioning
confidence: 91%
“…The electronic mechanisms involved in the HAVHA effect are treated in more detail in a submitted manuscript. 66 In this article we show the importance of such effect on magnetic shieldings in tin and lead tetrahalides family of compounds.…”
Section: 62mentioning
confidence: 91%
“…It can be seen in Table that the convergence of calculations using different basis sets is obtained with the MMA‐lresc basis set, which is an smaller version of aug‐cc‐pVTZ‐lresc basis set and was named aug‐Jun1 basis set in earlier works . The differences in the values of the total shielding, obtained as the addition of the NR shielding constant with all relativistic corrections, is smaller than 1 ppm compared with the values obtained using the larger basis set (aug‐cc‐pVTZ‐lresc).…”
Section: Applications Of the Lresc Modelmentioning
confidence: 95%
“…We also aim to have an insight on each correcting term, and finally on 2014 we proposed an overview to treat relativistic corrections grouped in two terms. We named those terms as core‐ and ligand‐dependent . We present in this section a brief account of LRESC achievements in describing heavy atom containing molecular systems.…”
Section: Applications Of the Lresc Modelmentioning
confidence: 99%
“…They were studied since 30 years ago for many research groups in a vast variety of molecular systems. However, few years ago a third heavy atom effect was proposed in our research group, termed the HAVHA (heavy‐atom effects on vicinal‐heavy‐atoms) effect . New studies were then needed to find enough evidence for this effect.…”
Section: Few Recent Applications Of Relativistic Polarization Propagamentioning
confidence: 99%
“…The electronic mechanisms that underlie these two terms are thus important in the HAVHA effect. We showed that the HAVHA effect is due to all three ligand‐dependent relativistic effects . The percentages of the SO correction for molecular systems containing tin as the central atom goes down.…”
Section: Few Recent Applications Of Relativistic Polarization Propagamentioning
confidence: 99%